PENDIDIKAN IPS SEBAGAI “SYNTHETIC DISCIPLINE”: KAJIAN EPISTEMOLOGIS ATAS PEMIKIRAN NU’MAN SOMANTRI - Mohammad Imam Farisi; Abdul Malik (LPMPP Universitas Negeri Yogyakarta, 2015)
Abstrak: Pemikiran seorang atau kelompok pakar merupakan bagian integral dalam dinamika sebuah disiplin ilmu, dan kajian terhadapnya telah menjadi concern dalam berbagai disiplin ilmu. Penelitian ini mengkaji secara epistemologis pemikiran Somantri tentang PIPS sebagai ‘synthetic discipline’. Penelitian bersifat kualitatif-interpretif dan menggunakan sumber data primer dan sekunder dengan teknik anotasi bibliografis dan reviu literatur serta dianalisis dengan teknik analisis konten kualitatif. Hasil penelitian menunjukkan bahwa secara epistemologis, PIPS dalam pemikiran Somantri dikonseptualisasi sebagai sebuah disiplin ilmu (DPIPS) dan program pendidikan disiplin ilmu (PDIPS) terintegrasi, hasil rekayasa sinergistis dari dua atau lebih disiplin ilmu yang setara untuk tujuan PIPS. PIPS sebagai disiplin ilmu terintegrasi adalah identitas, jati-diri, ciri khas, dan faculty culture FPIPS dan pascasarjana PIPS. PIPS sebagai DPIPS memiliki status akademik sebagai advance knowledge, middle studies, dan primary structure. PIPS sebagai program PDIPS memiliki status akademik sebagai PDIPS untuk jenjang pendidikan tinggi, dan PDIPS untuk jenjang pendidikan sekolah. Kata Kunci: epistemologi, pendidikan IPS, synthetic discipline SCIENCE EDUCATION AS “A SYNTHETIC DISCIPLINE”: AN EPISTEMOLOGICAL ANALYSIS OF NU’MAN SOMANTRI’S THOUGHT Abstract: An expert’s or group of experts’ thought is an integral part in the dynamics of a scientific discipline, and an analysis of it has become the concern of many scientific disciplines. This study analyzed epistemologically Somantri’s thought of social science as a ‘synthetic discipline”. This study was qualitative-interpretive and utilized primary and secondary sources using the annotated bibliographies and literature review. The data were analyzed using the qualitative content analysis. The findings showed that epistemologically, social science in Somantri’s thought was conceptualized as a scientific discipline and an integrated scientific discipline eduacational program. It was also a synergetic engineering product of two or more than two equivalent scientific disciplines for the purpose of social science education. Social science education as an integrated scientific discipline is the identity, typical characteristics, and the faculty culture of the social science education faculty and the social science education graduate program. Social science had the academic status as advanced knowledge, middle studies, and primary structure. Social science as had an academic status as a social science discipline in the tertiary education and in the secondary education. Keywords: epistemology, social science education, synthetic discipline